4′-Chlorodiazepam is neuroprotective against amyloid-beta in organotypic hippocampal cultures. Issue 171 (July 2017) - Arbo, B.D.; Hoppe, J.B.; Rodrigues, K.; Garcia-Segura, L.M.; Salbego, C.G.; Ribeiro, M.F.
Highlights: TSPO ligands have been used as neurotherapeutic agents in different models. Aβ-induced neurotoxicity is related with oxidative damage. 4′-CD protects organotypic hippocampal cultures against Aβ. This action may be related with increased protein expression of superoxide dismutase. Abstract: The translocator protein (TSPO) is an outer mitochondrial membrane protein involved in the transport of cholesterol into the mitochondria, which is the first step for the synthesis of steroid hormones, as well as in the regulation of mitochondrial permeability transition pore opening and apoptosis. Studies have shown that the activation of TSPO may promote neuroprotective actions in experimental models of neurodegeneration and brain injury. In a previous study, our group showed that 4′-chlorodiazepam (4′-CD), a TSPO ligand, was neuroprotective against amyloid-beta (Aβ) in SHSY-5Y neuroblastoma cells. The aim of this study was to evaluate if 4′-CD was also neuroprotective against Aβ in organotypic hippocampal cultures and to identify its mechanisms of action. Aβ decreased the cell viability of organotypic hippocampal cultures, while 4′-CD had a neuroprotective effect when administered at 100 nM and 1000 nM. The neuroprotective effects of 4′-CD against Aβ were associated with an increased expression of superoxide dismutase (SOD). No differences were found in the expression of catalase, glial fibrillary acidic protein, Akt and procaspase-3. In summary, our results show that 4′-CD is neuroprotective against Aβ by a mechanism involving the modulation of SOD protein expression.